Cognition in Situations. Issue 4 (24th August 2020) - Price, Taylor
Abstract : The symbolic interactionist tradition can contribute to advancing sociological studies of cognition by setting dual process models on more solid ground. I draw on Blumer's epistemological statements and the interactionist tradition more broadly to consider how dual process models of cognition could be applied to naturally occurring situations. I suggest that attending to the ways the past and the future are handled and modified within social interaction provides a usable inroad for the sociology of cognition to engage with situational analysis. I identify "resonance" and "iterative reprocessing" as concepts that are suitable to this end.